Scenarios of future land use change around United States' protected areas. (April 2015) - Martinuzzi, Sebastián; Radeloff, Volker C.; Joppa, Lucas N.; Hamilton, Christopher M.; Helmers, David P.; Plantinga, Andrew J.; Lewis, David J.
Highlights: We evaluated scenarios of future land use change around federal protected areas in the U.S. The most changes occurred around Wildlife Refuges, the least around Wilderness Areas. Land uses around Refuges and Forests were the most sensitive to changing scenarios. Urban expansion is likely to continue to threaten protected areas. Abstract: Land use change around protected areas can diminish their conservation value, making it important to predict future land use changes nearby. Our goal was to evaluate future land use changes around protected areas of different types in the United States under different socioeconomic scenarios. We analyzed econometric-based projections of future land use change to capture changes around 1260 protected areas, including National Forests, Parks, Refuges, and Wilderness Areas, from 2001 to 2051, under different land use policies and crop prices. Our results showed that urban expansion around protected areas will continue to be a major threat, and expand by 67% under business-as-usual conditions. Concomitantly, a substantial number of protected areas will lose natural vegetation in their surroundings. National land-use policies or changes in crop prices are not likely to affect the overall pattern of land use, but can have effects in certain regions. Discouraging urbanization through zoning, for example, can reduce future urban pressures around National Forests and Refuges in the East, while the implementation of an afforestation policy can increase the amount of natural vegetation around some Refuges throughout the U.S. On the other hand, increases in crop prices can increase crop/pasture cover around some protected areas, and limit the potential recovery of natural vegetation. Overall, our results highlight that future land-use change around protected areas is likely to be substantial but variable among regions and protected area types. Safeguarding the conservation value of protected areas may require serious consideration of threats and opportunities arising from future land use.